Strategi Memperkokoh Jantung Pendidikan Islam - M. Asep Fathur Rozi (Ta'allum: Jurnal Pendidikan Islam, 2017)
Islamic education is the responsibility of the community and the government. To raise and advance education then required strategy. One of them is a strategy to strengthen the heart Islamic education, namely educator, library, and laboratory. They are a source of learning that most powerful thing to build personality school tuition. Strategy strengthens educator could be done by monitoring and evaluation by institutions through an assessment performance and hold internal training and involve outside training. Then to complete function library could be done by furnish library collection and allocating funding to increase the collection and improving facilities and infrastructure library including photocopy, online access library, and search engine book. The strategy we can do for strengthening laboratory among others by preparing a laboratory technician that not only mastering in managing the laboratory but also in Islamic scientific, prepare facilities and infrastructure in the lab and obliges in educator to use laboratory by order to support their teaching.